Adverse effects of chemotherapy on the teeth and surrounding tissues of children with cancer: A systematic review with meta-analysis. (August 2018) - Busenhart, Dan Mike; Erb, Juliane; Rigakos, Georgios; Eliades, Theodore; Papageorgiou, Spyridon N.
Highlights: Indications of dental adverse effects from chemotherapy for childhood cancer exist. This systematic review summarizes dental and oral adverse effects of chemotherapy. Chemotherapy is associated with increased risk of dental anomalies like agenesis. Chemotherapy is also associated with decreased salivary flow and increased caries. Comprehensive hospital dental care might be needed for childhood cancer survivors. Abstract: Objective: The aim of this systematic review was to assess evidence on dental adverse effects associated with chemotherapy (CH) administered to children with cancer. Material and methods: Eight databases were searched without restrictions up to March 2017 for studies reporting on dental effects of CH administered for childhood cancer. After elimination of duplicates, data extraction, and risk of bias assessment according to the Cochrane guidelines, random-effects meta-analyses of Relative Risks (RR) and Mean Differences (MD) and their 95% Confidence Intervals (CI) were performed, followed by meta-regression and sensitivity analyses. Results: The literature search identified a total of 15 non-randomized case-control studies including at least 2315 patients (mean age at diagnosis or CH of 6.6 years; 36% male) followed for up to 22.9 years after CH. Meta-analysis indicated that CH was associated with increased risk for tooth agenesis compared to healthy controls (RR = 2.47; 95% CI = 1.30–4.71; P = 0.006). This translated to every seventh child with CH having agenesis of at least one tooth that would not otherwise have. Additionally, CH was significantly associated with increased risk of tooth discoloration, arrested tooth development, enamel hypoplasia, microdontia, premature apexification, and decreased salivary flow rate, as well as worse oral hygiene and greater caries experience compared to controls. However, the strength of evidence was very low due to the inclusion of non-randomized study designs with high risk of bias. Conclusions: Current evidence from childhood cancer survivors indicates that chemotherapy is associated with considerable dental adverse effects that might be associated with greater burden of disease and treatment costs.